Direct bioconversion of agricultural waste-rice straw into bioethnol by solid state bioconversion - Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed; Ismail, M. Hafiz (2007)
Bioethanol production was carried out by solid state bioconversion method utilizing lignocellulosic material, rice straw (RS) as substrate with the aid of mixed cultures of Saccharomyces cerevisiae, T. harzianum and P. chrysosporium. The mixed culture of the microorganisms was established to investigate their compatibility for direct bioconversion of rice straw into bioethanol. The results indicated that the yeast, Saccharomyces cerevisiae and fungal strains T. harzianum, and P. chrysosporium were found to be the most suitable strains for the ethanol production using rice straw as major substrate. From the observation and estimation of ethanol yield, T. harzianum and S. cerevisiae are mutually grows together in liquid and solid media and proved to be excellent in producing ethanol compared to other combinations. The highest production of bioethanol found as 10.1% on the sixth day where the highest reading was recorded for the combination of P. chrysosporium, T. harzianum and S. cerevisiae. The other parameters glucosamine content as growth indicator, reducing sugar released and the pH were measured to evaluate the bioconversion process.